Nonstructural protein 5B promotes degradation of the NORE1A tumor suppressor to facilitate hepatitis C virus replication. Issue 5 (30th March 2017) - Arora, Payal; Basu, Amartya; Schmidt, M. Lee; Clark, Geoffrey J.; Donninger, Howard; Nichols, Daniel B.; Calvisi, Diego F.; Kaushik‐Basu, Neerja
Abstract : Hepatitis C virus (HCV) infection is a common risk factor for the development of liver cancer. The molecular mechanisms underlying this effect are only partially understood. Here, we show that the HCV protein, nonstructural protein (NS) 5B, directly binds to the tumor suppressor, NORE1A (RASSF5), and promotes its proteosomal degradation. In addition, we show that NORE1A colocalizes to sites of HCV viral replication and suppresses the replication process. Thus, NORE1A has antiviral activity, which is specifically antagonized by NS5B. Moreover, the suppression of NORE1A protein levels correlated almost perfectly with elevation of Ras activity in primary human samples. Therefore, NORE1A inactivation by NS5B may be essential for maximal HCV replication and may make a major contribution to HCV‐induced liver cancer by shifting Ras signaling away from prosenescent/proapoptotic signaling pathways. Conclusion : HCV uses NS5B to specifically suppress NORE1A, facilitating viral replication and elevated Ras signaling. (Hepatology 2017;65:1462‐1477).